(untitled) (Journal for Studies in Humanities and Social Sciences, 2016)
Drawing illustrations chiefly from oral narratives, this article seeks to interrogate and dissect the imagining of violence in pre-colonial Shona society while paying special attention to the use of language of hatred, pain and injury therein. Language faithfully mirrors and gives away a society’s behavioural, spiritual, political, etc. construction. In view of the violence that has dogged Zimbabwe for several decades now, our point of departure is a polemical refutation of the traditionally held view that has one-sidedly idolised pre-colonial Shona society as peaceful and impliedly violence-free. While surely pre-colonial Shona society could never have been one marathon of violence, nevertheless, holding an analytical mirror to the past will reflect that the peaceful thesis does not constitute the whole truth either. The exaggerated image of a peaceful and innocent Shona society, we argue, was precipitated by a resurgent search for an African identity whose design was to reconnect with the past while countering the racist framing of blacks as a bloodthirsty lot to whose rescue the white man came. However folktales and romances, let alone pre-colonial history itself, betray, quite embarrassingly so for the one-sided view, as well as demonstrate that the Shona were not uniquely endowed with an incapacity for violence.